2018
DOI: 10.1002/cche.10070
|View full text |Cite
|
Sign up to set email alerts
|

Cereal bran extracts inhibit the formation of advanced glycation endproducts in a bovine serum albumin/glucose model

Abstract: Background and objectives The adverse health effects of advanced glycation endproducts (AGEs) is of current interest; some previous research indicates that consuming these compounds may contribute to chronic diseases such as diabetes and heart disease. The objective of this study was to determine whether cereal bran extract from wheat (Jagger, JA), triticale (Spring Triticale, ST, and Thundercale, TH), and Rye (RY) can inhibit the formation of AGE in a bovine serum albumin/glucose (BSA/GLU) model. Findings Nε‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The formation of the Maillard reaction is expedited in pH ranged 7.0-10.0 (Nursten, 2005). Furthermore, metal ions can significantly F I G U R E 1 Formation of N ɛ -carboxymethyllysine (CML) in foods during the Maillard reaction and alternative pathways of reactive glyoxal: (1) glycolytic pathway intermediates pathway; (2) Wolff pathway-glucose autoxidation; (3) sorbitol aldose reductase pathway; (4) Namiki pathway-Schiff's base cleavage; (5) Hodge pathway: Amadori product cleavage; (6) lipid peroxidation with reactive oxygen species (ROS) production; and (7) protein oxidation and modification with ROS production (adapted from G. Chen et al, 2018;Sergi et al, 2021; influence the reaction rate, where Kwak and Lim (2004) found Fe 2+ and Cu 2+ contributed to the browning formation in a model system. On the contrary, Ca 2+ and Mg 2+ could decrease the rate in light of their different water-binding capacity.…”
Section: Formation Of CML In Foodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The formation of the Maillard reaction is expedited in pH ranged 7.0-10.0 (Nursten, 2005). Furthermore, metal ions can significantly F I G U R E 1 Formation of N ɛ -carboxymethyllysine (CML) in foods during the Maillard reaction and alternative pathways of reactive glyoxal: (1) glycolytic pathway intermediates pathway; (2) Wolff pathway-glucose autoxidation; (3) sorbitol aldose reductase pathway; (4) Namiki pathway-Schiff's base cleavage; (5) Hodge pathway: Amadori product cleavage; (6) lipid peroxidation with reactive oxygen species (ROS) production; and (7) protein oxidation and modification with ROS production (adapted from G. Chen et al, 2018;Sergi et al, 2021; influence the reaction rate, where Kwak and Lim (2004) found Fe 2+ and Cu 2+ contributed to the browning formation in a model system. On the contrary, Ca 2+ and Mg 2+ could decrease the rate in light of their different water-binding capacity.…”
Section: Formation Of CML In Foodsmentioning
confidence: 99%
“…The Maillard reaction mainly leads to exogenous dietary CML, while the oxidation of protein and lipid markedly impacts CML formation beyond the reaction. Since the formation of CML depends on multifaceted factors (e.g., species, nutrient composition, and thermal cooking methods) (G. Chen et al., 2018; Zhu, Fang, et al., 2021), the present mitigation strategies include selecting different reactive compounds, adjusting processing methods, and adding desirable inhibitors.…”
Section: Strategies For Mitigating Dietary CMLmentioning
confidence: 99%
See 2 more Smart Citations